Construire sa place en haute vallée alpine française : S’installer et vivre dans des confins - Anne Barrioz (Territoire en Mouvement)
This article questions the arrival of new inhabitants in mountain areas, called here confines. This notion includes the remoteness of a space, the distance from main networks and urban centers, the accessibility to public services, etc. This reflection is based on a sample of 146 interviews, conducted in eight high Alpine valleys in France. The aim of this article is to question the ways that the inhabitants use to construct a new place in a context of marginality. We consider the high valley as a subjective isolated horizon which becoming a new place according to migrations and installations and depending on the inhabitants’ capacity to become integrated and on the territories’ capacity to welcome them. The reflection is based on the paths of life, called also trajectories. The inhabitants make the choice to isolate in order to live close to the mountains. They unveil the existence of amenity migrations in those valleys. Moreover, they develop a sensitive link with the territory and are also confronted with different difficulties, especially about moving and social integration. Building one’s own in high valley, according to idealized representations of mountains, requires a professional and personal adaptability, in particular to find an housing.